Transmission routes of visceral leishmaniasis in mammals - Vinícius Vasconcelos Gomes de Oliveira (Ciência Rural, 2015)
Visceral leishmaniasis (VL) is a chronic disease caused by Leishmania infantum. The major sites of parasite localization in infected animals are the secondary lymphoid organs, bone marrow and cutaneous tissue. However, reports exist on the detection of the parasite in the organs of the male and female genital system. The main route of transmission is related to the hematophagous sandfly vectors of the genus Lutzomyia(New World) and Phlebotomus(Old World). However, other routes of transmission may be mentioned, such as sexual, vertical, hematogenic without vector and others involved in VL epidemiology. Thus, the current article reviews the main forms of transmission of visceral leishmaniasis in mammals